Odpowiedzi

2010-03-07T10:10:29+01:00
A) 5x²-15x = 5x(x-3)
b) 8xy+8x = 8x(y+1)
c) 10a²-2ab = 2a(5a-b)
d) xy-xy² = xy(1-y)
e) 6a-2yb+3ac - tu się nic nie da "wyciągnąć" przed nawias
f) 12ab²+16b² = 4b^(3a+4)
g) x³-2x²+x = x(x^-2x+1)
h) 2xy+3x-x²y = x(2y+3-xy)
i) 5x-15xy-10 = 5(x-3xy-2)
2010-03-07T10:19:48+01:00
A) 5x²-15x = 5x(x-3)
b) 8xy+8x = 8x(y+1)
c) 10a²-2ab = 2a(5a-b)
d) xy-xy² = xy(1-y)
e) 6a-2yb+3ac =nie da sie xD
f) 12ab²+16b² = 4b^(3a+4)
g) x³-2x²+x = x(x^-2x+1)
h) 2xy+3x-x²y = x(2y+3-xy)
i) 5x-15xy-10 = 5(x-3xy-2)